EFEKTIVITAS STRATEGI PEMBELAJARAN MIND MAPPING TERHADAP PEMAHAMAN SISWA PADA SISTEM PEREDARAN DARAH DI SMP - Yonatan, Amandus; Ningsih, Kurnia; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe research is to determine the effectiveness of learning strategy â€œmind mappingâ€ on students' understanding on the material â€œcirculatory systemâ€ of eighth graders of Gembala Baik Pontianak Junior High School. The research uses quasi-experimental designs with nonequivalent control group design plan. The samples consist of two classes, VIII C as the experiment class and VIII E as the control class.Â  The researchâ€™s instrument used is 20 multiple choice items. The result indicatesÂ  the mind mapping strategyÂ  is better than expository strategy. The increasing of the mean score from 7.33 to 16.67 for the experiment class. And from 7.14 to 14.65 for the control class. From Mann-Whitney U test, Zcount < Ztable (-4.24 < -1.96),Â  there are differences of studentsâ€™ understanding. The result of Effect Size (0.92), gets the area of 0.3212 ( O-Z table). It means that the mind mapping learning strategy gives an effectiveness of 32.12% on studentsâ€™ understanding. Keyword: Effectiveness, mind mapping, learning strategy, students understanding, circulatory system